Functional hyperprolactinemia and subclinical primary hypothyroidism: myth or reality in clinical practice? - Giulia Bovo; Pierluigi Mazzeo; Giorgia Antonelli; Mattia Barbot; Filippo Ceccato; Irene Tizianel (Journal of Endocrinological Investigation, 2026)
Abstract Background Hyperprolactinemia is a frequent clinical condition with different etiologies. Although primary hypothyroidism is often considered a leading cause of mild hyperprolactinemia, the supporting evidence is limited and often based on small studies with single prolactin (PRL) measurement, especially in cases of subclinical hypothyroidism. This study aims to evaluate the prevalence of thyroid dysfunction in patients assessed for functional hyperprolactinemia. Patients and methods This retrospective study included patients undergoing cannulated PRL sampling (three measurements) and thyroid function assessment between January 2013 and May 2024, at Padova University-Hospital. Patients were stratified by PRL elevation and TSH levels. PRL-secreting pituitary adenoma and medication-induced hyperprolactinemia were exclusion criteria. Results Of 292 patients with available data, 229 fulfilled the inclusion criteria. Hyperprolactinemia was confirmed in 89/229 patients (39%). Among these, 26% had increased TSH compared to 16% in the normoprolactinemic group (p=0.083). PRL levels from cannulated samples and their mean values were not significantly higher in patients with hypothyroidism. No significant correlation was observed between TSH and PRL levels (Spearman’s rho=0.053; p=0.428). The absence of association between TSH and PRL levels was confirmed also in a subgroup analysis in women of reproductive age. Conclusion Our findings suggest that subclinical hypothyroidism is common in patients evaluated for hyperprolactinemia: mild TSH increase should not delay the diagnostic evaluation for hyperprolactinemia, due to the low likelihood of thyroid dysfunction as the cause of hyperPRL.